Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ta có 4x2 + 9y2 = (2x)2 +2 .2x.3y +(3y)2 -12xy
= (2x+3y)2 -12xy
thay 2x + 3y = 8 và xy = 2 có
82 -12. 2= 64-24 = 40
a. \(2a^2+5ab-3b^2-7b-2\)
\(=\left(2a^2+6ab+2a\right)-\left(ab+3b^2+b\right)-\left(2a+6b+2\right)\)
\(=2a\left(a+3b+1\right)-b\left(a+3b+1\right)-2\left(a+3b+1\right)\)
\(=\left(2a-b-2\right)\left(a+3b+1\right)\)
b. \(2x^2-7xy+x+3y^2-3y\)
\(=\left(2x^2-xy\right)-\left(6xy-3y^2\right)+\left(x-3y\right)\)
\(=x\left(2x-y\right)-3y\left(2x-y\right)+\left(x-3y\right)\)
\(=\left(x-3y\right)\left(2x-y\right)+\left(x-3y\right)\)
\(=\left(x-3y\right)\left(2x-y+1\right)\)
c. \(6x^2-xy-2y^2+3x-2y\)
\(=\left(6x^2+3xy\right)-\left(4xy-2y^2\right)+\left(3x-2y\right)\)
\(=3x\left(2x+y\right)-2y\left(2x+y\right)+\left(3x-2y\right)\)
\(=\left(3x-2y\right)\left(2x+y\right)+\left(3x-2y\right)\)
\(=\left(3x-2y\right)\left(2x+y+1\right)\)
a/ \(=3y^2-6y-2x+1\)
b/ \(=-\left(x^3-3x^2+3x-1\right)=-\left(x-1\right)^3\)
c/ \(=\left(2-x\right)^3\)
d/ \(=xy^2+x^2y+3xy+x^2y+x^3+3x^2-3xy-3x^2-9x\)
\(=xy\left(y+x+3\right)+x^2\left(y+x+3\right)-3x\left(y+x+3\right)\)
\(=\left(xy+x^2-3x\right)\left(y+x+3\right)=x\left(y+x-3\right)\left(y+x+3\right)\)
e/ \(=xy-x^2+2x-y^2+xy-2y\)
\(=x\left(y-x+2\right)-y\left(y-x+2\right)=\left(x-y\right)\left(y-x+2\right)\)
a) =(2x+3y-1)2
b)=-(x-1)3
c)=-(x3-6x2+12x-8)=-(x-2)3
d)x3 + 2x2y + xy2 – 9x
= x(x2 + 2xy + y2 -9)
= x[(x2 + 2xy + y2) - 32]
= x[(x + y)2 - 32]
= x (x + y – 3)(x + y + 3)
e) 2x-2y-x2+2xy-y2=2(x-y)-(x-y)2=(x-y)(2-x+y)
Bạn dùng hằng đẳng thức ý
a. (A – B)2= A2 – 2AB+ B2
b. (A – B)2= A2 – 2AB+ B2
c. (2x+3y)(2x-3y)-(2x+y)2
= 4x2-9y2 -4x2 - 4xy-y2
= -10y2-4x2
d. (A+B)2 = A2+2AB+B2
a ) \(\left(3x-1\right)^2+\left(3x+1\right)^2+2\left(3x+1\right)\left(1-3x\right)\)
\(=\left(1-3x\right)^2+\left(3x+1\right)^2+2\left(3x+1\right)\left(1-3x\right)\)
\(=\left(1-3x+3x+1\right)^2\)
\(=2^2=4\)
b ) \(\left(2x-3y\right)^2+\left(2x+3y\right)^2+\left(2x-3y\right)\left(2x+3y\right)\)
\(=4x^2-12xy+9y^2+4x^2+12xy+9y^2+4x^2-9y^2\)
\(=\left(4x^2+4x^2+4x^2\right)+\left(9y^2+9y^2-9y^2\right)+\left(12xy-12xy\right)\)
\(=12x^2+9y^2\)
a,(2x-y)2+(2x+y)2=(2x2-2*2xy+y2)+(2x2+2*2xy+y2)
=2x2-4xy+y2+2x2+4xy+y2
=4x2+2y2
\(\left(x+y\right)^3-x^3-y^3\)
\(=x^3+3x^2y+3xy^2+y^3-x^3-y^3\)
\(=3x^2y+3xy^2\)
\(=3xy\left(x+y\right)\)
\(a,\left(2x+3y\right)^2-4\left(2x+3y\right)\)
\(=\left(2x+3y\right)\left(2x+3y-4\right)\)
\(b,\left(x+y\right)^3-x^3-y^3\)
\(=\left(x+y\right)^3-\left(x^3+y^3\right)\)
\(=\left(x+y\right)\left[\left(x+y\right)^2-\left(x^2-xy+y^2\right)\right]\)
\(=\left(x+y\right).3x\)
\(c,\left(x-y+4\right)^2-\left(2x+3y-1\right)^2\)
\(=\left(x-y+4+2x+3y-1\right)\left(x-y+4-2x-3y+1\right)\)
\(=\left(3x+2y+3\right)\left(-x-4y+5\right)\)